Environmental Microbiome: A Sustainable Tool for Building Climate Resilience in Agroecosystems - Raj, Hans; Giri, Krishna; Kumar, Sanjeev; Mishra, Gaurav; Singh, Sanjay; Singh, Manish Kumar; Kumar, Manoj (Indian Forester, 2024)
As the changing climate continues to pose significant challenges to global agriculture, scientists and policymakers have to develop suitable strategies to enhance the resilience of agroecosystems. Microorganisms inhabiting the soil environment have emerged as a promising solution for building climate-resilient agroecosystems due to their versatile nature. Microorganisms inhabiting in different ecological niches in agroecosystems have been studied widely for their direct and indirect role in maintaining plant and soil health and increasing crop productivity. Harnessing the multifarious properties of soil microorganisms has tremendous potential to enhance the productivity and sustainability of the agroecosystems in one hand and mitigate the adverse effects of climate change on the other. This review paper aims to present an overview of the role of microbes in promoting soil health, nutrient cycling, carbon sequestration, pest management and building resilience in agroecosystems.